RELATIONSHIP BETWEEN LOW ACTIVITY OF DAILY LIFE AND LONELINESS OF GERIATRICS IN IKOT- EKPENE METROPOLIS, AKWA IBOM STATE, NIGERIA - Ogundoyin , Oluwaseun Dare; Oke , Tunde Dayo; Bala , Faruk; Dalyop , Yusuf; Edem , Usenobong Donald; Ogundoyin , Mariam Ebele (Journal of Professional Counselling, 2022)
The study investigated the relationship between low activity of daily life and loneliness of geriatrics in Ikot- Ekpene metropolis, Akwa Ibom state, Nigeria. The study employedcorrelational design. A total of three hundred (300) old people comprising 104 males and 199 females, whose age ranged between 60 years and 81 years were used in the study. A self-administered and close-ended questionnaire containing gender and age, Geriatric Loneliness Scale (á = .75) and Activity of Daily Life Scale (á = .71) were used in collecting data from the participants. Data collected was analysed using simple percentage and Pearson product moment correlation. The result revealed that low activity of daily life significantly correlated with loneliness of geriatrics; and that the level of loneliness increased as chronological age increased. Based on the result, it was concluded that low activity of daily life significantly correlated with loneliness of geriatric in Ikot- Ekpene metropolis, Akwa Ibom state, Nigeria.